Beginning Blockchain A Beginner's Guide to Building Blockchain Solutions - Singhal, Bikramaditya (Apress, 2018)
Understand the nuts and bolts of Blockchain, its different flavors with simple use cases, and cryptographic fundamentals. You will also learn some design considerations that can help you build custom solutions. Beginning Blockchain is a beginner's guide to understanding the core concepts of Blockchain from a technical perspective. By learning the design constructs of different types of Blockchain, you will get a better understanding of building the best solution for specific use cases. The book covers the technical aspects of Blockchain technologies, cryptography, cryptocurrencies, and distributed consensus mechanisms. You will learn how these systems work and how to engineer them to design next-gen business solutions. What You'll Learn: Get a detailed look at how cryptocurrencies work Understand the core technical components of Blockchain Build a secured Blockchain solution from cryptographic primitives Discover how to use different Blockchain platforms and their suitable use cases Know the current development status, scope, limitations, and future of Blockchain.